Arabic Vocabulary Learning Strategies in Early Childhood: A Case Study at an Integrated Islamic Elementary School - Sri Zulfida; Zainal Rafli; Fathiaty Murtadho; Mohammad Shahidul Islam (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2024)
This study explores the strategies and methods for teaching Arabic vocabulary to young children at an Integrated Islamic Primary School (SDIT). The research analyzes how different teaching approaches affect vocabulary acquisition in early childhood education. A qualitative descriptive method was used, with data collected through classroom observations, in-depth interviews, and document analysis. The main strategies identified include visual and audio media, thematic approaches, repetition, and interactive games. The results highlighted that multisensory and Total Physical Response (TPR) methods significantly improved vocabulary retention and student participation. The communicative approach also proved effective in helping students use new vocabulary in practical contexts. The findings suggest combining visual, physical, and verbal techniques is the most effective way to improve vocabulary acquisition. This study contributes to the ongoing discourse on language learning by providing insights into effective vocabulary teaching strategies in an Islamic educational setting, with implications for curriculum development and teacher training.